Effect of Dried Medicinal Crops on the Performance and Carcase Flavour of Broilers - Dahal, I.M.; Farran, M.T. (International Journal of Poultry Science, 2011)
The present study was planed to evaluate the effect of adding 2% of Mint, Thyme and Cardamom to the broiler finisher diet for 0, 6, 12 and 18 days before slaughter at 42 days old on the performance, carcase yield and meat flavouring using the two-way ANOVA method for means analysis. The final results showed that there was no significant negative affect for the dried medicinal crops on the performance and carcase traits. On the other hand a significant (p